A Case Report of Klebsiella sepsis in an Infant with Goldenhar Syndrome: Association or Coincidence (Indian Journal of Child Health, 2020)
Goldenhar syndrome (GS) is a rare congenital disorder of the development of first and second branchial arches. The born neonate may exhibit orofacial, auricular, skeletal, and solid organ involvement with variable phenotypic expression. The pathogenesis and long-term implication of GS is still under study. Multidisciplinary management is the key in lifelong management of GS. There is a challenge identifying this syndrome in low-resource setting. We describe in this case report about a neonate with typical phenotypic features and late-onset Klebsiella sepsis.